E-learning initiatives in Malaysia (PowerPoint presentation) - Asirvatham, David; Woods , Peter; Takahashi, Kenzo; Kaur, Abtar (2003)
Development of e-learning in Malaysia - E-learning Survey Report - Case study: Multimedia Learning System at Multimedia University